7(x-5)+10=5(2x-5)-3x

Simple and best practice solution for 7(x-5)+10=5(2x-5)-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(x-5)+10=5(2x-5)-3x equation:



7(x-5)+10=5(2x-5)-3x
We move all terms to the left:
7(x-5)+10-(5(2x-5)-3x)=0
We multiply parentheses
7x-(5(2x-5)-3x)-35+10=0
We calculate terms in parentheses: -(5(2x-5)-3x), so:
5(2x-5)-3x
We add all the numbers together, and all the variables
-3x+5(2x-5)
We multiply parentheses
-3x+10x-25
We add all the numbers together, and all the variables
7x-25
Back to the equation:
-(7x-25)
We add all the numbers together, and all the variables
7x-(7x-25)-25=0
We get rid of parentheses
7x-7x+25-25=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 11a+16=3a | | -3+10y=-81 | | 6x-6=2+22 | | 3/10s=61/6 | | 6w+9=3 | | -7x-7(x+6)=10 | | -x-5+4x=1 | | 12x+12x+12x+12x+12x=x+7+6x+9+x+-10 | | 7r+11=5+r | | 5x-23=2x=4 | | -15/4=4x+5x-6 | | 8x+9x-46=69-6x | | 10(u+2)=100 | | y/12+2=-11 | | 6-9w=3 | | 5x-8+3x=-64 | | 65=11x-17 | | 5w-15=-20 | | 5-3(x+3)=7(x-2) | | 8x+9x=69-6x | | 10+9m=-62 | | 7-6m=43 | | -21-6x=-x+14 | | 43=7–-6m | | 2x+3-6x=-41 | | 56=7(z-78) | | -2(1-5r)=13+7r | | -5+9z=1-2z | | 6+4y=62 | | 3/2c=15 | | 5v+9=79 | | 3x-19=37-5x |

Equations solver categories